Clean and fast cross-coupling of aryl halides in one-pot - Pandarus, Valerica (Beilstein-Institut, 2014)
Unsymmetrically coupled biaryls are synthesized in high yield starting from different aryl bromides and bis(pinacolato)diboron by carrying out the Miyaura borylation reaction followed by the Suzuki–Miyaura reaction in the same reaction pot over 1–2 mol % SiliaCat DPP-Pd. The SiliaCat DPP-Pd catalyst is air-stable and the method does not require the use of inert conditions. The use of non-toxic isopropanol or 2-butanol as reaction solvent further adds to the environmental benefits of this new green synthetic methodology.